1987
DOI: 10.1177/154193128703100111
|View full text |Cite
|
Sign up to set email alerts
|

Designing Airline Passenger Safety Cards

Abstract: The field of human factors endeavors to optimize and standardize interfaces in achieve the best fit possible, to include the design of instructional material. The authors an attempt to have observed that airline passenger safety cards vary greatly in layout, construction, etc. and could benefit from quidelines presented in the pertinent literature. The present effort examined both user preference as well as card effectiveness. It was found that cards which implement recommended techniques are more preferred an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…[ [40][41][42] Diagrams that display a series of sequential steps are more successful for comprehension of a process than one single graphic. [43,41] Use a color-contrasted word or statement for text that should be read first and/or be perceived as more urgent than the rest, unless color is used for other reasons (e.g., bilingual text).…”
Section: Warning Messages: Visual Modementioning
confidence: 99%
“…[ [40][41][42] Diagrams that display a series of sequential steps are more successful for comprehension of a process than one single graphic. [43,41] Use a color-contrasted word or statement for text that should be read first and/or be perceived as more urgent than the rest, unless color is used for other reasons (e.g., bilingual text).…”
Section: Warning Messages: Visual Modementioning
confidence: 99%
“…Although some research has found that accompanying text does not provide any additional help in comprehension (e.g., Burt, Henningsen and Consedine 1999), no research was found showing that the provision of text hinders response. Research does suggest that a minimum number of words should be used to accompany graphics (Caird et al 1997;Schmidt and Kysor 1987). Also, if applicable, diagrams that display a series of sequential steps (that are numbered) are more successful in comprehension of a process than one single graphic (Burt, Henningsen and Consedine 1999;Caird et al 1997).…”
Section: Comprehending the Pictorial/graphic If Usedmentioning
confidence: 99%
“…Although some research found that accompanying text does not provide any additional help in comprehension (e.g., Burt, Henningsen and Consedine 1999), no research was found that the provision of text hinders response. Research does suggest that a minimum number of words should be used to accompany graphics (Caird et al 1997;Schmidt and Kysor 1987). Also, if applicable, diagrams that display a series of sequential steps (that were numbered) are more successful in comprehension of a process than one single graphic (Burt, Henningsen and Consedine 1999;Caird et al 1997).…”
Section: Comprehending the Pictorial/graphic If Usedmentioning
confidence: 99%